2022
DOI: 10.1371/journal.pone.0274066
|View full text |Cite
|
Sign up to set email alerts
|

Association between retinitis pigmentosa and an increased risk of primary angle closure glaucoma: A population-based cohort study

Abstract: Background Retinitis pigmentosa (RP) is the most frequent retinal hereditary dystrophy and result in blindness if progresses. Several case reports have revealed the possible association between RP and primary angle-closure glaucoma (PACG). We conducted a population-based study to explore whether RP significantly increased the risk of PACG development. Methods Using the Taiwan National Health Insurance Research Database, we enrolled patients with RP into the RP group from 2001 to 2013 and included a compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A common form of glaucoma found in RP is primary angle-closure glaucoma (PACG), with prevalence rates between 1.0% and 2.3% [ 262 , 263 , 264 ]. Previous studies have shown that the association between RP and PACG are related to nanophthalmos, short axial length, cataract and lens subluxation [ 263 ]. Anatomically, patients with a short axial length and/or cataract have a relatively shallow anterior chamber more prone to occlusion.…”
Section: Management Of Rp-associated Complicationsmentioning
confidence: 99%
“…A common form of glaucoma found in RP is primary angle-closure glaucoma (PACG), with prevalence rates between 1.0% and 2.3% [ 262 , 263 , 264 ]. Previous studies have shown that the association between RP and PACG are related to nanophthalmos, short axial length, cataract and lens subluxation [ 263 ]. Anatomically, patients with a short axial length and/or cataract have a relatively shallow anterior chamber more prone to occlusion.…”
Section: Management Of Rp-associated Complicationsmentioning
confidence: 99%
“…While the association of primary open-angle glaucoma in RP is known, people with RP are also at a significantly higher risk of developing primary angle-closure glaucomas. [ 5 , 6 ] One possible explanation is the underlying genetic factors leading to dystrophic changes both in the trabecular meshwork and retina. It has been noted that these patients may have a tendency toward accelerated lens growth, which can contribute to a higher risk of angle-closure glaucomas.…”
mentioning
confidence: 99%
“…[ 7 ] There is also a higher risk of lens subluxation in patients with RP, which can further aggravate narrow angles. [ 5 ]…”
mentioning
confidence: 99%